Seismic resilience of building inventory towards resilient cities - Juan Gustavo Salado Castillo; Michel Bruneau; Negar Elhami-Khorasani (Resilient Cities and Structures, 2022)
Resilience of a community after an extreme event depends on the resilience of different infrastructure including buildings. There is no well-established approach to characterize and integrate building resilience for community-level applications. This paper investigates how different potential functionality measures can be used to quantify building resilience indexes, and how the results could be aggregated for a set of buildings to provide an indicator for the resilience of an entire community. The quantification of building resilience is based on different functionality measures including repair cost, occupancy level, and asset value. An archetype city block with four different buildings is defined. The individual results for each building are combined using a weight-based approach to quantify the resilience index for the city block. The study then considers small-scale communities with different number of buildings to investigate the influence of contractor availability and collapse probability on the resilience indexes for the set of buildings. Both parameters are shown to be important when quantifying the resilience index. It is also demonstrated that the overall resilience of a community is directly influenced by the resilience of individual buildings. The findings presented here are useful both from the perspective of quantifying the resilience of a community on the basis of its building inventory, as well as for possible inclusion into a holistic framework that aims to quantify community resilience.